Locking of southward extrusion in favour of rapid crustal-scale buckling of the Greater Himalayan sequence, Nar valley, central Nepal - Godin, L; Gleeson, T; Searle, M; Ullrich, T; Parrish, R (2006)
The South Tibetan detachment system (STDS) bounds the upper limit of the Greater Himalayan sequence (GHS), which consists of the exhumed middle crust of the Himalaya. In the Annapurna range of central Nepal, the GHS comprises a sequence of amphibolite-grade augen gneisses with a 3.5 km thick leucogranite at the higher structural levels (Manaslu granite). Two major low-angle normal-sense shear zones have been mapped. The Chame detachment has similar grade metamorphic rocks above and below and is interpreted as a ductile shear zone wholly within the GHS. The Phu detachment is a ductile-brittle normal fault which wraps around the top of the Manaslu leucogranite and defines the uppermost, youngest strand of the STDS, placing folded unmetamorphosed Palaeozoic rocks of the Tethyan sedimentary sequence above the GHS. Our data indicate that ductile flow and southward extrusion of the GHS terminated with cessation of movement on the brittle upper strand of the Phu detachment at c. 19 Ma, which was followed almost immediately by crustal-scale buckling. Argon thermochronology reveals that the bulk of the metamorphic rocks and lower portions of the Tethyan sedimentary sequence in the Nar valley cooled through the hornblende, biotite and muscovite closure temperatures at c. 16 Ma, suggesting very rapid cooling rates. The thermochronology results indicate that this cooling occurred 2-3 million years earlier than in the frontal part of the extruded GHS. Although the extrusion in the frontal part of the GHS must have locked at the same time as in the Nar valley, the exhumation there was slower, and most probably only assisted by erosion, rather than by rapid folding as is the case in the Nar valley. This buckling indicates a step northward in deformation within the Himalayan belt, which may be a response to a lower deforming taper geometry in the foreland. © The Geological Society of London 2006.